QUIET QUITTING PHENOMENON AT SMP THE INDONESIA NATURAL SCHOOL TEACHERS AS A FORMAL EDUCATIONAL INSTITUTION THAT CARRIES AN MERDEKA BELAJAR SYSTEM - Retno Nurulia Hapsari; Agung Surya Dwianto (Jurnal Bina Bangsa Ekonomika, 2024)
This research was made to identify the emergence of the quiet quitting phenomenon, the contributing factors associated with the trend of work-life balance, and the follow-up impacts that happen in an educational institution through a qualitative-descriptive method approach with data collection through interviews and literature studies.. The results showed that most employees are indicated to have done quiet quitting due to various reasons, such as efforts for work-life balance to reduce the level of burnout or stress due to workloads that are not proportional to compensation and expectations, which results in the level of job satisfaction continuing to drop. However, employees in an educational institution that promotes Merdeka Belajar curriculum are demanded to constantly make a variety of teaching and learning innovations, be responsive in dealing with the changing era, responsive in dealing with educational problems, and continue to develop their own capacity as educators and agents of change. Therefore, teachers and school staff should not lose their passion and enthusiasm for work to increase their motivation to make the Merdeka Belajar movement a successful program for the sake of Indonesian education and the betterment of the nation